Self-assembly silicon/porous reduced graphene oxide composite film as a binder-free and flexible anode for lithium-ion batteries. (20th February 2015) - Tang, H.; Zhang, Y.J.; Xiong, Q.Q.; Cheng, J.D.; Zhang, Q.; Wang, X.L.; Gu, C.D.; Tu, J.P.
Abstract: A Si/porous reduced graphene oxide (rGO) composite film synthesized by evaporation and leavening method are developed as a high-performance anode material for lithium ion batteries. The porous structure as buffer base can effectively release the volume expansion of the silicon particles, increase the electrical conductivity and reduce the transfer resistance of Li ions. The Si/porous rGO composite film presents high specific capacity and good cycling stability (1261 mA h g −1 at 50 mA g −1 up to 70 cycles), as well as enhanced rate capability. This approach to prepare such a unique structure is a low-cost and facile route for the silicon-based anode materials.